Experimental and numerical investigation of wave induced motions of partially submerged bodies approaching a fixed structure. (1st May 2018) - Sayeed, Tanvir; Colbourne, Bruce; Molyneux, David; Akinturk, Ayhan; Zaman, Hasanat
Abstract: Estimation of iceberg impact load is an important design consideration for offshore structures in ice prone regions. Impact velocity is influenced by the complex hydrodynamic interaction between the iceberg or bergy bit and the offshore structure. In order to understand the phenomenon, a two phase, experimental and numerical, study has been conducted. In the first phase, the change in wave loads on different sized spherical model ice masses was investigated for different proximities to a fixed structure and the results published in Sayeed et al. (2017b). This paper describes the results of the second phase study where the change in wave induced motions of free floating ice masses, approaching a fixed structure, is investigated through physical experiments and numerical simulations. The experiments were carried out at the Ocean Engineering Research Center (OERC) of Memorial University of Newfoundland and the motions were measured using an optical tracking system, Qualysis © . The objective is to determine the velocity profiles of approaching ice masses and how that changes prior to impact. The experimental results of motion data show excellent correlation with the force data gathered in the first phase. Similar to previous studies, the separation distance to wavelength ratio is shown to dictate the corresponding wave induced motions. As the body gets close to the structure, the surge motion slows and at the same time the heave motion is increased. Some experiments have also been conducted to understand the effect of initial starting location on the resulting drift velocity. Numerical simulations of the experimental cases, using the commercial CFD software Flow3D ©, show good agreement with the experimental data. Highlights: Experimental and numerical studies on wave induced motions of a small body approaching a fixed structure. Motion results show excellent correlation withforce data (Sayeed et al. (2017b)). The seperation distance to wavelength ratiodictates the surge and heave motions. Flow3D can capture hydrodynamic interaction effect of a small body moving towards a fixed structure.